Additive Manufacturing of Electronics from Silver Nanopowders Sintered on 3D Printed Low‐Temperature Substrates. Issue 4 (25th January 2021) - Wałpuski, Bartłomiej; Słoma, Marcin
Abstract : Additive manufacturing is more widely used these days in aerospace, power industry, and automotive. The latest reports indicate that electronics can be produced with this technique. This approach requires the development of new materials for the fabrication of conductive metallic layers on polymers. Herein, a hybrid technique based on fused deposition modeling, direct‐write, and selective laser sintering is demonstrated, for the fabrication of structural electronics. Highly conductive paths are obtained with conductivity values up to 3.2·10 6  S m −1 in a single printing and sintering additive process. The influence of process parameters is evaluated with several 3D printed polymer substrates affecting the electrical conductivity of the printed conductive paths and circuits. The developed hybrid technique allows performing selective thermal sintering of metallic pastes on polymer substrates exhibiting the value of melting temperatures much lower than the sintering temperature of the silver paste. This phenomenon can be explained with the proposed hypothesis that the activation energy of the sintering process of metallic paste and degradation of polymer substrate plays a key role in obtaining functional conductive metallic paths on polymer substrates. Application of the developed process is demonstrated with a simple human interface device and a circuit with light‐emitting diodes and power source. Abstract : Additive manufacturing is widely used these days in aerospace and automotive. Herein, various additive techniques are combined to fabricate electronics. The developed hybrid technique allows performing laser sintering of metallic pastes on polymer substrates in which melting temperatures are much lower than paste sintering temperature. Explanation of this phenomenon is proposed and application of the developed process is demonstrated.